Psychometric Properties of the Independent and Interdependent Self-Construal Questionnaire: Evidence From the Czech Republic - Lacko, David; Čeněk, Jiří; Urbánek, Tomáš (Frontiers in Psychology, 2021)
This article introduces a validation study of the Czech version of an independent and interdependent self-construal questionnaire (SCS, Vignoles et al., 2016) conducted on 330 Czech subjects. In this study, the reliability, convergent validity and factor validity were verified. However, the confirmatory factor analysis revealed unsatisfactory factor structure (RMSEA = 0.053 [0.048, 0.057], SRMR = 0.080, CFI = 0.775, TLI = 0.755). These results are discussed with respect to other adaptations of individualism/collectivism scales in countries beyond typical West-East dichotomy. Hence, the article not only critically discusses the shortcoming of the Czech and original versions of the questionnaires, but also the general issues of the individualism-collectivism construct in the cross-cultural context as a whole.